EFFECT OF ECONOMIC DETERMINANTS OF TAX COMPLIANCE ON TAX REVENUE IN NIGERIA - Ogagaoghene John Agana; Ifeoma Mary Okwo; Ama Ibiam Obasi; Sarah Taiwo Agana (Asosiasi Dosen Muda Indonesia, 2026)
Nigeria’s tax revenue remains relatively low compared to its potential, suggesting persistent compliance gaps. Strengthening compliance through enforceable economic and administrative mechanisms is therefore critical for improving domestic revenue mobilization. Objective: This study investigates the extent to which selected economic determinants of tax compliance tax audit probability, interest on late and non-payment of taxes, tax filing rate, and tax rate influence tax revenue in Nigeria. Methodology: The study adopts an ex-post facto quantitative design using annual time-series data (1990–2020) sourced from the Federal Inland Revenue Service (FIRS) and the Central Bank of Nigeria (CBN) Statistical Bulletin. The relationships between the explanatory variables and tax revenue were examined using multiple regression analysis (SPSS). Findings: Results indicate that tax audit probability, interest on late and non-payment of taxes, tax filing rate, and tax rate each have a positive and statistically significant effect on tax revenue in Nigeria. The model suggests that reductions in these determinants are associated with corresponding declines in tax revenue, underscoring their relevance for revenue performance. Implications: The findings imply that improving audit coverage and effectiveness, strengthening enforcement of interest charges for defaults, and increasing taxpayer filing compliance can enhance revenue outcomes. Policy efforts should prioritize risk-based auditing, timely filing enforcement, and administrative measures that reduce non-compliance. Originality: This study contributes evidence from a long-run Nigerian dataset by jointly testing multiple compliance-related economic determinants within one empirical framework, offering integrated insight for tax administration reforms aimed at improving revenue generation.